Aggregation‐enhanced theranostics: AIE sparkles in biomedical field. Issue 1 (29th December 2020) - Kang, Miaomiao; Zhang, Zhijun; Song, Nan; Li, Meng; Sun, Panpan; Chen, Xiaohui; Wang, Dong; Tang, Ben Zhong
Abstract: Theranostics referring to the ingenious integration of diagnostics and therapeutics has garnered tremendous attention in these years as it provides a promising opportunity for modern personalized and precision medicine. By virtue of the good biocompatibility, outstanding fluorescence property, easy processability and functionalization, promoted photosensitizing efficiency, as well as facile construction of multi‐modality theranostics, fluorophores with aggregation‐induced emission (AIE) characteristics exhibit inexhaustible and vigorous vitality in the field of theranostics. Numerous significant breakthroughs and state‐of‐the‐art progression have been witnessed in the past few years. This review highlights the tremendous aggregation‐enhanced superiorities of AIE luminogens (AIEgens) in disease theranostics mainly involving diagnostic imaging (fluorescence and room temperature phosphorescence), therapeutic intervention (photodynamic therapy), and feasibility in construction of multi‐modality theranostics based on the experimental measurements and theoretical simulations. Additionally, the latest and advanced developments of AIEgens in disease theranostics in the aspect of corresponding strategies to design highly effective AIE‐active theranostics through triggering aggregation formation are comprehensively summarized. Moreover, a brief conclusion with the discussion of current challenges and future perspectives in this area is further presented. Abstract : A new concept of aggregation‐enhanced theranostics (AET) is put forward on the basis of tremendous aggregation‐enhanced superiorities of AIEgens in terms of diagnostic imaging, therapeutic intervention, and feasibility in construction of multi‐modality one‐for‐all theranostics. Additionally, the latest and advanced developments in the fields of AET based on AIEgens referring to strategies to trigger aggregation formation are comprehensively summarized.